Exploring Fungal Diversity and distribution in Dukan Freshwater Lake Using ITS rDNA-based PCR Cloning/ Sequencing - Hamad, Ibrahim Sulaiman; Arif, Huner Hiwa; Khidir, Kamal Ahmad (Sulaimani Journal for Pure and Applied Sciences, 2017)
Fungi represent important trophic inhabitants in aquatic ecosystems, they have crucial roles in nutrient cycling in freshwater ecosystems. In the present study, Internal Transcribed Spacer ITS rDNA-based investigations of fungal communities in Dukan Lake were conducted from two collection sites using large-scale clonal Sanger sequencing. Herein we report for the first time, the composition of fungal communities in water samples of Dukan Lake through cloning/sequencing method. A total of 576 clones were obtained from ITS gene library and resulted in retrieving of 33 fungal operational taxonomic units (OTUs). The majority of clone sequences belonged to Ascomycota while members of other fungal phyla were recovered at much lower frequencies. Molecular diversity analysis in Dukan Lake revealed the existence of fungi belonged to Pleosporales, Hypocreales, Helotiales, Mortierellales, Eurotiales, whereas Capnodiales, Onygenales, Pezizales, and Xylariales were detected in relatively minor abundances in the Dukan Lake ecosystem. In conclusion, molecular techniques using ITS rDNA-based PCR cloning/ sequencing is currently used as an effective tool to investigate the complex fungal communities in the aquatic systems however additional studies using next generation sequencing are needed for descriptive details regarding the occurrence and abundance of fungi in aquatic environments.
Keywords: Aquatic fungi; Clone; Detection; Metagenomics; Taxonomy